The COL27A1 and COL11A1 gene variants are not associated with the susceptibility to anterior cruciate ligament rupture in Polish athletes - Zhuo Sun; Aleksandra Bojarczuk; Pawel Cieszczyk (Baltic Journal of Health and Physical Activity, 2023)
Introduction: Sports injuries are the most common cause of anterior cruciate ligament (ACL) ruptures. Previous research has demonstrated links between some of the COL27A1 and COL11A1 genetic variants and musculoskeletal soft tissue injuries. However, no previous research has investigated the COL27A1 rs1570460 and the COL11A1 rs3753841 in the context of ACL rupture in any population. Thus, our study aimed to assess the association between specific single nucleotide polymorphisms (SNPs), i.e., COL27A1 rs946053 and COL11A1 rs3753841, and the occurrence of ACL injury (ACL-I) in a cohort of Polish athletes. Methods: The study enrolled 233 athletes with ACL-I (161 males and 71 females) and 228 healthy control athletes (143 males and 85 females) with no prior ACL-I history. Genotyping was conducted to assess the presence of COL27A1 rs946053 and COL11A1 rs3753841 genetic variants. Statistical analyses were performed using the R programming environment and package, and an association between SNPs and ACL-I was tested in four genetic models: dominant, co-dominant recessive, and over-dominant. Results: All the analyzed polymorphisms conformed to Hardy-Weinberg equilibrium (HWE). The study revealed no significant differences between the ACL-I and control groups. Conclusions: Despite the absence of significant associations between the investigated SNPs and ACL-I in this study, our findings highlight the importance of continued research to unravel the precise genetic risk mechanisms and etiological factors contributing to ACL-I.